The dialectics of jungle people and modern law in the life of the jungle people in Jambi province Indonesia - Itmam, Muhammad Shohibul (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper explains the dialectic of the family law of the jungle and modern law in the midst of the social struggle of the people who experience changes in legal awareness as a consequence of interaction with external law or modern law. Using qualitative, descriptive, and analytical approach; as a field research that focuses on legal awareness, this paper concludes that there has been a major change in the legal awareness of the family of the jungle people who initially still used ancestral doctrine received from their parents for generations to the law accommodating and assimilative. These changes are actually the impact of a long struggle that specifically occurred in the transition period leading up to reform until now. This is very likely to occur continuously and dynamically according to changes in the awareness of the next family law that is influenced by the social context of society that occurs between them. In addition, the dynamics of family law awareness in the jungle of the people in Jambi was supported by the policies of the Jambi provincial government and national and global developments.